MOTIVASI PETANI MENANAM WORTEL (Daucus carota L.) DI DESA GAJAH KECAMATAN SIMPANG EMPAT KABUPATEN KARO - Roida Ervina Sinaga; Sarah Gracia; Nabila Syahmita; Inka Ilfana (JURNAL AGROTEKNOSAINS, 2023)
Farmers' motivation to plant carrots (Daucus carota L.) in Simpang Empat District, Karo Regency. Carrot (Daucus carota L.) is one of the leading commodities in Karo Regency. The motivation of farmers as carrot plant business developers is a situation that spurs farmers to do a business, what is the basis for farmers to plant carrots, obstacles in growing carrots and what benefits can be obtained from planting carrots. The aims of the research were to find out: (1) farmers' motivation in planting carrots; (2) factors influencing farmer motivation; (3) the relationship between the factors that influence motivation and the motivation of farmers in planting carrots. The research method is a quantitative method with survey techniques. The research is located in Simpang Empat District, Karo Regency. Sampling using accidental sampling technique as many as 20 farmers. Motivation was analyzed using a questionnaire based on assessment criteria in an effort to find out how the level of motivation of farmers in planting carrots (Daucus carota L.) in Simpang Empat District, Karo Regency